Pelaksanaan Pembelajaran di MA & MTs Aisyiyah Palembang - Aulia, Ifa; Sumah , Astrid Sri Wahyuni (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2023)
The use of learning models can help realize an effective learning process, but whether all teachers in the online or face-to-face learning process are limited to implementing learning models. The purpose of this study was to determine the methods and models of learning as well as what obstacles in the application of learning models during face-to-face were limited. The subjects in this study were Integrated Biology and Science teachers at MA and MTs Aisyiyah Palembang. While the samples of this study were one Biology teacher at MA Aisyiyah Palembang and two Integrated Science teachers at Mts Aisyiyah Palembang. Data collection techniques using observation, interviews and documentation. The results of this study are the learning methods in MA and MTs Aisyiyah Palembang, namely the lecture, discussion, question and answer and scientific methods. While the demonstration method is not applied. The learning models used by biology teachers at MA and MTs Aisyiyah Palembang are the Discovery Learning, Program Based Learning and PjBL models. The problem is that the teacher has difficulty managing the time, that is, one hour lesson is only 30 minutes, so it is difficult to apply the model syntax. So the solution is that the teacher must be creative in choosing the right model and have skills in managing the class so that learning objectives can be implemented. Keywords: Learning Methods and Models, Biology Teachers, Obstacles in the application of learning models